Macroeconomic, Financial Performance, COVID-19, and the Stability of Islamic Rural Banks: Regional Evidence from Indonesia - Rokhmah, Fatma Nur; Rusgianto, Sulistya (Jurnal Ekonomi Syariah Teori dan Terapan, 2025)
This study aims to analyze the effect of macroeconomic, financial performance, and the COVID-19 pandemic on the stability of Islamic Rural Banks (BPRS) in Indonesia, as well as to examine the differences in these effects between the Java and non-Java regions. A quantitative approach using panel data regression (Random Effect Model) was applied to data from 100 BPRS during the 2020–2024 period. Financial stability was measured using the Z-score. Macroeconomic variables include provincial inflation and regional GDP growth (PDRB). Financial performance indicators consist of Capital Adequacy Ratio (CAR), Financing-to-Deposit Ratio (FDR), and Non-Performing Financing (NPF), while the COVID-19 dummy variable captures the impact of the pandemic shock. The empirical results show that CAR and NPF have a significant influence on BPRS stability across all regions, while inflation and PDRB are not statistically significant in the aggregate model. The COVID-19 variable exerts a significant negative effect on stability, confirming the pandemic’s disruptive impact on Islamic microfinance. When the model is estimated separately for Java and non-Java regions, the FDR variable demonstrates a stronger and negative effect on stability in non-Java BPRS, indicating structural disparities in liquidity management and risk absorption capacity. These findings underline the importance of region-specific macroprudential and microprudential policies, particularly in enhancing capital strength and liquidity governance among non-Java BPRS. The study contributes to the literature on Islamic financial stability by integrating macroeconomic, financial, and crisis dimensions within a regional framework, offering strategic implications for the Financial Services Authority (OJK) and Bank Indonesia to strengthen the resilience of Islamic microfinance institutions in Indonesia